The Influence of Economic Factors and Regulatory Environment on Strategic Business Decisions at the Regional Secretariat of West Sumatra Province - Azizah, Hidayatul Putri; Vadhillaesa, Shania; Naldi, Rio; Ichsan, Muhammad; Aima, M. Havidz (Riset Sinergi Indonesia, 2025)
This article explores the influence of economic factors and the regulatory environment on strategic business decisions at the Regional Secretariat of West Sumatra Province. In a rapidly changing landscape, understanding these influences is essential for effective governance and public administration. Key economic indicators such as Gross Domestic Product (GDP), inflation rates, and employment statistics are analyzed to assess their impact on resource allocation and priorities within the Secretariat. Additionally, the article examines the regulatory frameworks established by both national and regional governments, highlighting the importance of compliance and stakeholder engagement in decision-making processes. The findings indicate that economic pressures can lead to prioritization of essential services, while regulatory challenges necessitate innovative solutions and strategic partnerships. By leveraging economic insights and navigating the regulatory landscape, the Secretariat can enhance its capacity to respond to community needs and achieve development goals. Recommendations for improving strategic planning include regular economic analysis, stakeholder collaboration, and flexibility in decision-making. Ultimately, this study aims to provide a comprehensive understanding of how economic and regulatory factors shape the strategic direction of the Regional Secretariat, fostering more effective and resilient public administration in West Sumatra.